PERAN TINGKAT SUKU BUNGA DEPOSITO DAN PENINGKATAN JUMLAH DEPOSITO DI PT BPR CIPTA CEMERLANG INDONESIA (CCI) - Latuni, Fandy (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
It cannot be denied that the progress of a country in development is very dependent on the banking world, remembering that in 1998 along with the Indonesian economic crisis along with the destruction of the Indonesian banking world. Collecting funds from customers and channeling to debtors is the bank’s main task. In normal circumstances, this will be one of the supporting factors in development. The interest rate becomes a determining factor in people’s interest in choosing a bank to deposit their funds in the form of savings or deposits. The purpose of this study is to find out whether interest rates influence the increase in the amount of deposits in the bank of PT BPR Cipta Cemerlang Indonesia (CCI) in Manado. Based on the results obtained stated that the deposit interest rate does not affect the amount of deposits at PT BPR Cipta Cemerlang Indonesia (CCI).